The Taxonomy of Goal-oriented Actions in Virtual Training Environments - Fardinpour, Ali; Reiners, Torsten (Elsevier BV, 2014)
With the shift of training scenarios to virtual worlds and assessment being an inevitable part of any teaching and learning process, we require sophisticated assessment methods to analyze action-sequences of learners according to reference solutions defined by experts and provide automated formative feedback. We propose the ‘Action-based Learning Assessment Method’ (ALAM) using an action taxonomy to classify recognized actions performed by the user in the virtual world. Most of these taxonomies were developed to model the behavior and performance of users. Yet, current taxonomies of human actions were developed based on need in specific research, still lacking a general taxonomy. The taxonomy of goal-oriented actions in virtual training environments was developed to overcome this problem and will be discussed in this paper.